Potential tuberculostatic agents: Micelle-forming copolymer poly(ethylene glycol)-poly(aspartic acid) prodrug with isoniazid - Silva, M. [UNESP]; Lara, A. S.; Leite, C. Q.F. [UNESP]; Ferreira, E. I. (My University, 2001)
With the objective of obtaining slow-acting isoniazid derivatives, of potential use as chemoprophylactics or chemotherapeutics in tuberculosis, the micelle-forming copolymer of poly(ethylene glycol)-poly(aspartic acid) prodrug with isoniazid was synthesized. The derivative obtained was found to be active in Mycobacterium tuberculosis culture, with a minimal inhibitory concentration (MIC) 5.6 times lower than that of the tuberculostatic drug.
Keywords: Co-polymer poly(ethylene glycol)-poly(aspartic acid); Isoniazid; Micelle-forming polymer; Potential tuberculostatic agent; Prodrug